Effectiveness of Reading Drills on the Comprehension Skills of Grade One Pupils - Goto, Justine Joy (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to determine the effectiveness of reading drills on the comprehension skills of Grade One pupils at Mabuhay Homes 2000 Elementary School during School Year 2025–2026. The study employed a quasi-experimental research design utilizing a single-group pretest-posttest approach. Thirty Grade One pupils served as respondents and were described in terms of sex, sibling position, number of children in the family, monthly family income, parents’ educational attainment, and parents’ occupation. Parallel forms of pretest and posttest were used to measure the pupils’ comprehension skills before and after exposure to reading drills.The findings revealed that most of the respondents were male, first- or second-born children, and belonged to families with two or more children and average monthly income. Most parents were college undergraduates, employed, or self-employed. The pretest results indicated that the pupils’ level of comprehension skills was satisfactory, while the posttest results showed an improvement to a very satisfactory level. A significant difference was found between the pretest and posttest scores, indicating that reading drills effectively enhanced the comprehension skills of the pupils. Furthermore, no significant differences were found in the posttest results when grouped according to their demographic profile, suggesting that the effectiveness of reading drills is consistent regardless of pupils’ personal and family characteristics.Based on these findings, it is concluded that reading drills are an effective instructional strategy for improving the comprehension skills of Grade One pupils. The study recommends that teachers regularly incorporate varied reading drill activities in classroom instruction and develop appropriate reading materials to further enhance pupils’ learning. The implementation of the proposed action plan is encouraged, and future research may consider using a two-group experimental design to further validate the effectiveness of reading drills.